2015
DOI: 10.1159/000369521
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15, a Master Piece in the Immunological Jigsaw of Celiac Disease

Abstract: Background: The immune response causing celiac disease (CD) depends on the activation of intestinal CD4+ T cells by gluten-derived peptides presented by HLA-DQ2 or HLA-DQ8 molecules, the main genetic risk factor. However, additional factors are necessary to impair immune tolerance to dietary gluten, to stimulate intraepithelial lymphocytes (IEL) and to induce intestinal damage. Key Messages: Current data point to a central role of interleukin-15 (IL-15). In situ and ex vivo studies indicate that IL-15 stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 63 publications
2
17
0
2
Order By: Relevance
“…(1) are consistent with the idea that signals derived from both innate and adaptive cells regulate the activation of innate lymphocytes in nonlymphoid tissues, and thereby contribute to mucosal inflammation and disease (6,7,9,12,15,16). This lymphocyte cross-talk is an intriguing model for the amplification of adaptive immunity and raises important mechanistic questions (further information is provided in refs.…”
Section: Gliadin-specific T Cells May Activate Iels In Celiac Diseasesupporting
confidence: 81%
“…(1) are consistent with the idea that signals derived from both innate and adaptive cells regulate the activation of innate lymphocytes in nonlymphoid tissues, and thereby contribute to mucosal inflammation and disease (6,7,9,12,15,16). This lymphocyte cross-talk is an intriguing model for the amplification of adaptive immunity and raises important mechanistic questions (further information is provided in refs.…”
Section: Gliadin-specific T Cells May Activate Iels In Celiac Diseasesupporting
confidence: 81%
“…In addition to TCRαβ + CD8αβ + IEL, innate-like IEL lacking surface TCR expression were involved in the development of villous atrophy in patients with refractory CeD, 113 115 an indolent or cryptic innate intraepithelial lymphoma that rarely complicates CeD. In both active and refractory CeD, upregulation of IL-15 in the epithelium is thought to play a critical role in the activation of IEL and epithelial cell destruction 81 , 116 , 117 . In line with a role for IL-15 in promoting tissue destruction, a study showed that when mice overexpressing IL-15 in the epithelium were crossed to ovalbumin-specific CD4 TCR transgenic mice, they developed villous atrophy when ingesting ovalbumin 118 .…”
Section: Iel Function During Pathologymentioning
confidence: 99%
“…Enteropathy-associated T-cell lymphoma arising in the setting of CD is considered as the end phase of a biological process characterized by the development of an intraepithelial T-cell clone that first gives rise to sustained cytolytic attack, then develops genetic abnormalities and finally progresses to a clinically and histologically aggressive neoplasm. 13 In this scenario, the onset of a T-cell lymphoma with the features of EATL within the setting of adult AE is of great interest, even though only 1 report is present in the literature, possibly because of the rarity of this condition. 2 Herein, we describe the second case where, after a long course of clinical, serological, and histological remission, the appearance of a monoclonal rearrangement of the TCR-γ was followed by a rapid transition to an overt lymphoma carrying the classic CD30 marker and expressing the cytotoxic molecules.…”
Section: Discussionmentioning
confidence: 99%